Reimagining Finland as a manufacturing base: the nearshoring potential of Finland in an industry 4.0 perspective - Kaivo-Oja, Jari; Knudsen, Mikkel Stein; Lauraéus, Theresa (Business, Management and Economics Engineering, 2018)
After decades of globalization and outsourcing the idea of “bringing manufacturing back home” and the twin concepts of backshoring and nearshoring have received much attention in recent years. Recent positive stories from the Finnish manufacturing industry suggests Finland as an attractive target for nearshoring, yet little to none has hitherto been made of this connection. This article (i.) examines recent relocation literature with a focus on nearshoring and manufacturing in high-cost environments, (ii.) explores the location advantage of Finland, (iii.) analyses cases of recent manufacturing developments in Finland within this context as single incidents or signals of change, and (iv.) discusses this development within the perspective of Industry 4.0.